Molecular tensegrity: predicting 1,3-X–-X distance in gas-phase MXn (n <= 4) compounds from atomic sizes - Ganguly, Parthasarathy (Current Science, 2006)
This article extends an earlier definition(1) and use of molecular tensegrity for obtaining quantitatively the 1,3-non-bonded distances in gas-phase MX2 compounds to nearly 160 gas-phase MXn (n <= 4) inorganic compounds (including those of transition metal elements), once a transferable `core' atomic size is specified. The simple principles behind this methodology (involving only linear equations), its quantitative character, its transparency, its portability and its generality account very simply for molecular geometry in such compounds without requiring earlier theoretical methodologies. We also establish clear distinction in the prescription for obtaining the 1,3-distance when M is an atom of a metallic or insulating element.
Keywords: Atomic size; gas phase; molecular tensegrity; non-bonded distance